Collective motion and dynamic self-assembly of colloid motors. (May 2018) - Lin, Zhihua; Gao, Changyong; Chen, Meiling; Lin, Xiankun; He, Qiang
Abstract: Collectively dynamic self-assembly arising from the living mobility is the fundamental process of lives. Inspired by collective behaviors of living systems, collective motion and self-assembly of synthetic colloid motors have been brought into focus due to high performance and emerging phenomena beyond the power of single colloid motor. Here, we summarize the recent progress on the collectively dynamic self-assembly systems of synthetic colloid motors sorted by various triggers of self-propulsion and external fields (such as chemicals, light, electric fields, and acoustic fields), ranging from the propulsion to stimuli of collective self-assembly. The typical physical phenomena are presented, including phase separation, clustering, and giant number fluctuations. The collectively dynamic self-assembly of colloid motors are expected to provide unlimited opportunities to various applications with continuous innovation both in the design of synthetic colloid motors and the modulation of collectively dynamic self-assembly. Graphical abstract: Unlabelled Image Highlights: Recent progress in the collective dynamic self-assembly of colloid motors. Remarkable phenomena in the collective motions are analyzed. Dynamic self-assembly from self-propulsions and collisions are discussed. Collective motions by chemical reactions and physical stimuli are summarized. Perspectives on the development and applications of collective colloid motors are given.